Spinal fixation after laminectomy in pigs prevents postoperative spinal cord injury. Issue 2 (22nd February 2022) - Slot, Emma M. H.; de Boer, Bart; Redegeld, Saskia; van Thoor, Sander; Moayeri, Nizar; Slooff, Willem‐Bart; Schaafsma, Irene A.; Meij, Björn; van Doormaal, Tristan P. C.
Abstract: Background: A safe, effective, and ethically sound animal model is essential for preclinical research to investigate spinal medical devices. We report the initial failure of a porcine spinal survival model and a potential solution by fixating the spine. Methods: Eleven female Dutch Landrace pigs underwent a spinal lumbar interlaminar decompression with durotomy and were randomized for implantation of a medical device or control group. Magnetic resonance imaging (MRI) was performed before termination. Results: Neurological deficits were observed in 6 out of the first 8 animals. Three of these animals were terminated prematurely because they reached the predefined humane endpoint. Spinal cord compression and myelopathy was observed on postoperative MRI imaging. We hypothesized postoperative spinal instability with epidural hematoma, inherent to the biology of the model, and subsequent spinal cord injury as a potential cause. In the subsequent 3 animals, we fixated the spine with Lubra plates. All these animals recovered without neurological deficits. The extent of spinal cord compression on MRI was variable across animals and did not seem to correspond well with neurological outcome. Conclusion: This study shows that in a porcine in vivo model of interlaminar decompression and durotomy, fixation of the spine after lumbar interlaminar decompression is feasible and may improve neurological outcomes. Additional research is necessary to evaluate this hypothesis. Abstract : An effective and ethically sound animal model is essential for preclinical research to investigate spinal medical devices. Eleven pigs underwent a spinal interlaminar decompression (ILD) with durotomy. We report the initial failure of the model and show that fixating the spine with Lubra plates is a potential solution to prevent neurological deficit. Additional research is necessary to evaluate this hypothesis.